SPECIFIC CHARACTERISTICS AND IMPORTANCE OF INTERNET SPORTS JOURNALISM IN UZBEKISTAN - Toshkhujaev Z.A (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Sports today has become a huge movement that covers the people of every country in the world. On the one hand, sport is a means of demonstrating the potential and power of countries in the international arena, on the other hand, it is a factor of healthy education of the population, especially young people, and on the other hand, life itself shows that it has taken the form of a large business structure. Journalism, as the main social institution satisfying any society’s need for information, has to "collide" with the sports field. In this process, the task of sports journalism, which is becoming more and more popular, is also expanding dramatically. This article examines the specific features and importance of sports journalism in Uzbekistan.